Intracranial Tuberculomas: Presenting Symptoms and Outcome with Anti Tuberculosis Drugs Treatment - Afridi, Ehtisham Ahmed Khan; Naz, Shabana; Khan, Baynazir; Naeem, Shagufta; Naz, Raisa; Bhatti, Sajid Nazir; Sultan, Saad; Hussain, Sajid (International Journal of Pathology, 2018)
Background: Tuberculosis is still common in developing countries, and sometimes involves central nervous system, proper diagnosis and early treatment effectively reduces the mortality and morbidity associated with this diseaseObjective: Observe presenting symptoms and outcome on anti-tuberculosis drug treatmentMaterial and Methods: This prospective study was conducted in the Department of Neurosurgery in collaboration with Department of Pathology, Ayub Teaching Hospital Abbottabad from March 2010 to December 2016. 22 patients; 8 females and 14 males were studied for their signs & symptoms and outcome after anti-tuberculosis drug treatment.Results: The most common location of tuberculous lesions was supratentorium (81%) particularly in parietal lobe (50%) followed by frontal lobe (22.7%) and occipital lobe (18.2%). 45% patients had prior history of tuberculosis. Headache was the predominant complaint (72.7%) followed by altered sensorium (31%), seizures (27.3%) and cranial nerve palsies (22.7%). After 12 months of anti-tuberculosis treatment ATT, about 87% of patients had either resolved or regressed tuberculoma.Conclusion: Brain tuberculomas are benign lesions with” malignant” behavior. Early diagnosis and anti-tuberculosis drug treatment can effectively treat this lesion forever. So in developing countries like Pakistan, when there is cystic, nodular or multiple lesions, there should be suspicion for brain tuberculoma and work up should be done because of very good prognosis associated with anti-tuberculosis drug treatment.